BUSINESS STRATEGY ANALYSIS FOR PRIVATE HOSPITALS AMID A DIGITAL TRANSFORMATION (CASE STUDY OF RUMAH SAKIT MKK) - Qurratuaini, Hanifa; Novani, Santi (Kompetensi (Competence : Journal of Management Studies), 2023)
The purpose of this research is to investigate and analyze the current status of digital medical records in Rumah Sakit MKK and the readiness of healthcare professionals toward a digital transformation, to identify the challenges and barriers the hospital faces in digitizing its medical records and implementing a digital transformation, to evaluate the benefits and potential impact of digitizing medical records on Rumah Sakit MKK, and to provide recommendations and guidelines for other hospitals in Indonesia to successfully implement a digital transformation and improve their healthcare services. This study primarily employs qualitative methods to examine diverse viewpoints, pinpoint systemic challenges, and develop actionable remedies concerning the digital transformation of Rumah Sakit MKK. The primary methodology employed will be SSM (Soft System Methodology). The results showed that the current digital ecosystem combines physical and digital medical records, with the hospital still storing many physical medical records. The benefits of fully digitizing medical records in Rumah Sakit MKK are as streamlined processes, reduced expenses, improved operational efficiency, and stablished connectivity with Satusehat, a central government platform for digital medical records, thus complying with government regulations. The challenges faced by Rumah Sakit MKK in digitizing medical records is procurement challenge related to additional servers and PCs needed to support the digitization process, staff skillsets challenge related to the inadequate IT skills, particularly among older medical staff, and communication challenge to ensure that every stakeholders are aware of the transformation. The strategies defined to ensure a smooth digital transformation at Rumah Sakit MKK is facilitate the storage, management, and controlled access to medical records, involve key stakeholders, operate while following government regulations, guaranteeing data security, maintaining confidentiality, and adhering to healthcare standards, establish connectivity with Satusehat, a central government platform for digital medical records, encompass both physical and digital medical record storage, and constrained by government regulations, industry standards, technological advancements, and the imperative for interoperability within the healthcare sector.